Piezoelectric ZnO thin films for 2DOF MEMS vibrational energy harvesting - Tao, Kai (2020)
Zinc oxide (ZnO) is an environmental-friendly semiconducting, piezoelectric and non-ferroelectric material, and plays an essential role for applications in microelectromechanical systems (MEMS). In this work, a fully integrated two-degree-of-freedom (2DOF) MEMS piezoelectric vibration energy harvester (p-VEH) was designed and fabricated using ZnO thin films for converting kinetic energy into electrical energy. The 2DOF energy harvesting system comprises two subsystems: the primary one for energy conversion and the auxiliary one for frequency adjustment. Piezoelectric ZnO thin film was deposited using a radio-frequency magnetron sputtering method onto the primary subsystem for energy conversion from mechanical vibration to electricity. Dynamic performance of the 2DOF resonant system was analyzed and optimized using a lumped parameter model. Two closely located but separated peaks were achieved by precisely adjusting mass ratio and frequency ratio of the resonant systems. The 2DOF MEMS p-VEH chip was fabricated through a combination of laminated surface micromachining process, double-side alignment and bulk micromachining process. When the fabricated prototype was subjected to an excitation acceleration of 0.5 g, two close resonant peaks at 403.8 and 489.9 Hz with comparable voltages of 10 and 15 mV were obtained, respectively.